The renin-angiotensin system in healthy human platelets: expressed but inactive - François Panosetti; François M. Cuenot; Damian S. Saint Auguste; Ana C. Martins Cavaco; Allancer D. C. Nunes; Philip H. J. Lu; Céline Magrini; Max Molot; Gabriel Sanglard; Rodi Günçü; Yassine Zouaghi; Charles Béguelin; et al. (Platelets)
Platelets play a crucial role in arterial thrombus formation, offering potential for new antiplatelet therapies with reduced bleeding risk. Here, we investigated the role of the renin-angiotensin system (RAS) in human platelets and explored its potential link to COVID-19 coagulopathy. Experiments were performed ex vivo on healthy human platelets. The expression of RAS receptors (Mas, MrgD, ACE, ACE2, AT1 and AT2) was evaluated using western blot and immunofluorescence. Platelets were incubated in vitro with either Captopril or different RAS peptides including Alamandine, Angiotensin-I, Angiotensin-II, Angiotensin-(1–7), and Angiotensin-(1–9). Platelet adhesion was measured by spectrophotometry using BCECF fluorescence. Platelet activation and aggregation were analyzed using aggregometry after stimulation with extracellular matrix proteins. ACE and ACE2 activity were assessed using Fluorescent Peptides (FPS). We demonstrated that healthy human platelets express all the tested RAS receptors. However, RAS peptides did not modulate platelet adhesion or aggregation despite a wide range of concentrations tested. ACE activity was detected in platelet lysates, but it was not inhibited by Captopril, while ACE2 activity was undetectable. Our findings suggest that while RAS receptors are expressed in platelets, RAS peptides do not impact platelet function, at least in our experimental setting. COVID-19 coagulopathy may occur independently of the RAS.